Valor nutritivo de silagens de gramíneas de inverno com ou sem leguminosas e da planta de soja - Dias, Fábio Jacobs (2007)
Three experiments were carried out to accomplish this work. The trial I objective to evaluate the effects of the use of winter cereals silages cultivated alone or mixed with legumes on silage quality, dry matter intake, milk production and composition in dairy cows. The Experiment II objective to evaluate the potential of the triticale (X Triticosecale Wittmack) crop on grazing with dairy cows, on the production and quality of the biomass and post-grazing grain yield. The Trial III objective to evaluate the chemical composition, aerobic stability and total dry matter losses of soybean silage (Glycine max (L.) Merrill) at different reproductive stages of harvest. Trial I and II were conducted in Institut National of la Recherche Agronomique - INRA, Poitou-Charentes Research Center, in Lusignan-France. Trial III was carried out in Mandaguaçu, northwest of Paraná State, and in the Feed Analysis Laboratory and Animal Metabolism of Animal Science Department of Universidade Estadual de Maringá. In trial I twenty four Prim.Hosltein dairy cows in lactation were used, with milk average production of 24.4 kg, fed with grasses silages associated with legumes in three treatments: 1 - triticale silage (X Triticosecale Wittimack) (TS), 2 - triticale silage plus pea forage (Pisum arvensis L.) (TSfP) and 3 - triticale silage in mixture with oats (Avena sativa L.), vetch (Vicia sativa L.) and pea forage (TSOVfP). The animals were distributed in three lots of eight cows each (four primiparous and four multiparous). The experimental period lasted 63 days with three periods of 21 days each. The TSOVfP silage was superior on intake, digestibility and milk production in relationship to other silages. The fermentative characteristics of the silages were similar to the expected patterns for grasses silages in mixture with legumes. The DM average losses with the use of tracer sacks were higher in TSOVfP silage, with high losses in silo surface (26%). The triticale silage in mixture with legumes can be used on dairy cows feeding. Trial II sixteen Prim'Hosltein dairy cows were used, under triticale grazing from April 19 to May 2 of 2006. The used method was the destructive and indirect (disk meter of forage) in the evaluation of the forage mass, and there was positive correlation between the methodologies. The dry matter intake was estimate with the n-alkanes methodology. The mean intake and milk production values were of 17 kg DM/day and 24.6 liters of milk cow/day, respectively. The post-grazing grain yields accounted for 78; 51; 44 and 32% of the surface control that produced 5.11 t/ha. The triticale can be used in order to double purpose, grazing and grain harvest. The trial III was divided in two evaluation periods, 2005 and 2006 harvests. Four reproductive stages (R3, R4, R5 and R6) were determined as treatment in 2005 and three reproductive stages (R5, R6 and R7) in 2006. In 2005, there were differences (P<0.05) in the reproductive stages for dry matter amounts, ash, organic matter, crude protein, lignin, ether extract and buffering capacity. However it was not observed differences for neutral detergent fiber, acid detergent fiber, neutral detergent insoluble nitrogen, acid detergent insoluble nitrogen, cellulose, total carbohydrate and pH. In 2006, there was no effect of the ensilage reproductive stage on dry matter amounts, ash, organic matter, crude protein, neutral detergent fiber, acid detergent fiber, ether extract and total carbohydrate in function of the soybean harvest stage. The silages in R5 presented better quality, in both years 2005/2006. The soybean silage evidenced stability.